Macroscopic Fungal Diversity in Oil Palm Plantations in Buasom Village, Unurum Guay District, Jayapura Regency, Jayapura Papua - Raunsay, Edoward Krisson; Dorsila Iwanembut; Supeni Sufaati; Dolfina Costansah Koirewoa; Apriani Herni Rophi (PT FORMOSA CENDEKIA GLOBAL, 2024)
One of the unidentified fungi that occupy habitats or are found in oil palm lands. The importance or urgency of this research is carried out so that various types of fungi in Papua can be properly identified so as to enrich mushroom research data in various types of habitats. This study aims to determine the types and diversity of macroscopic fungi (fungi) found in oil palm plantations in Buasom Village, Unurum Guay District, Jayapura Regency. This study used 5 transects and each transect consisted of 5 observation plots which would be placed in oil palm plantations. The total number of observation plots is 25 with a size of 20 m x 20 m. The collected data will be analyzed using the K, KR, F, FR, INP and H' approach. The results showed that the composition of macroscopic mushroom species in the oil palm plantation of Buasom village, Unurum Guay District, Jayapura Regency as a whole was 24 species of mushrooms in 13 families. The number was distributed in the observation transect, namely, in the first transect 11 species with (H' 2.01) moderate category, in the second transect 7 species with (H' 1.81) low category, in the third transect 12 species with (H' 2.19) medium category, transect fourth 7 species with (H' 1.71) low category and fifth transect 5 species with (H' 1.31) low category